Changes in E-learning from a Social Perspective - Zbigniew Meger (Center for Open and Multimedia Eduacation of the University of Warsaw, 2011)
Evaluation of cognitive psychology ideas leads to turn us in direction of constructivist conceptions. It appears in current research studies, that the construction of knowledge in each learners mind is strongly supported by social processes and by well-organized group work. On the other hand we see a dynamic development of community education portals and other educational services in Web. The meeting of these two achievements may lead to changes in the concepts of work organization in educational processes. The paper presents constructivist analysis of new social networking tools and creates examples of applying them in modern education.